Analisis Dampak Perang Dagang AS–Tiongkok terhadap Volume Ekspor Minyak Sawit Mentah (CPO) Indonesia ke Tiongkok - Ade Surya Prasetyo; Ni Ketut Budiningsih; Putu Yusi Pramandari (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
Indonesia is the world’s largest producer and exporter of crude palm oil (CPO), with China as its primary strategic trading partner. The US–China trade war initiated in 2018 created a structural shock in global trade that potentially affected Indonesia’s CPO exports. This study analyzes the effects of Indonesian CPO Production, International CPO Prices, the IDR/USD Exchange Rate, and the US–China Trade War on Indonesia’s CPO export volume to China over the period 1990–2023, using the Error Correction Model (ECM) through the Engle-Granger two-step procedure. Results show that simultaneously all variables significantly affect CPO export volume to China. Partially, Indonesian CPO Production has a positive and significant effect in the long run (coefficient = 1.35), while International CPO Prices and the IDR/USD Exchange Rate show no significant effect. The US–China Trade War proved to have a significant negative effect in the short run (coefficient = -0.3099; p = 0.060), indicating a decline in Indonesia’s CPO export volume growth to China of approximately 30.99% during the conflict period, yet showed no significant effect in the long run, reflecting the resilience of bilateral CPO trade against global protectionism shocks. The ECT coefficient of -0.8484 indicates that approximately 84.84% of short-run disequilibrium is corrected toward equilibrium within one year.